ECOLOGICAL CHARACTERISTICS OF ANOLIS HOMOLECHIS (COPE, 1864) (SQUAMATA: DACTYLOIDAE) IN THE NATIONAL ECOLOGICAL RESERVE "MOGOTES DE JUMAGUA", VILLA CLARA, CUBA - Armiñana-García, Rafael (2021)
An ecological study of Anolis homolechis (Cope, 1864) (Squamata: Dactyloidae), a Cuban endemic reptile, is presented in the "Mogotes de Jumagua" National Ecological Reserve, located in the municipality of Sagua la Grande, Villa Clara province. The following parameters were taken into account: substrate, activity period, ecomorphs, diet, courtship and population; in addition, sympatric species were determined. This species was observed using tree trunks, shrubs, soil and stones, and presented its major activity between 11:01 am and 12 m. It also showed preference for feeding on insects, especially hymenoptera, and was found in cohabitation with four other anole species, although without establishing competition for the substrate.